Thomas Hardy and the Proper Study of Mankind - Gatrell, Simon. author. aut Link
IX, 195 p.
Keywords: Explores Hardy's account in fiction of the individual man or woman's relationship with various aspects of the encompassing world - with other individual men and women, with the aggregation known as society, with the natural and artificial environment and with the supernatural.